EFFECTIVENESS OF WASTEWATER TREATMENT IN THE CENTER OF THE WATERSHED OF THE OUTBREAK OF THE DANGER OF POVERTY IN THE NORTHERN PROVINCE OF BANYUMAS - Gita Nagiyanti; Taufik Purboyo; Emiraldo Win Pazqara (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Research with the title Effectiveness of Waste Handling at the Kamandaka Recycling Center, Bobosan Village, North Purwokerto District, Banyumas Regency. The research objective was to analyze and describe the effectiveness of waste handling at PDU Kamandaka, Bobosan Village, North Purwokerto District, Banyumas Regency using descriptive qualitative research methods. Determination of informants using purposive sampling technique. Collecting data through observation, interviews and documentation. Data analysis used Miles and Huberman's interactive model (2014:14). This study uses a system theory approach Gibson et al, 2000:34 which includes aspects of production, efficiency, satisfaction, adaptation and development. The results of the study show that waste management at PDU Kamandaka is not yet effective because there are still several aspects that are not effective. It is hoped that the waste that enters the Kamandaka PDU after undergoing the processing process will run out, but in reality the waste cannot be processed as a whole because the sources used in waste processing include man, money, material, machine, method, & market that are not in accordance with what programmed. Based on the results of the research conducted, it can be concluded that waste management at Kamandaka PDU has not been effective because the waste processing process has not been able to achieve the regional policy and strategy targets for Banyumas Regency, namely 30% waste reduction and 70% waste handling. Based on the research results, it can be recommended first, the waste processing process has not been able to reduce the volume of incoming waste, the solution is to increase the number of PDUs in Banyumas Regency, especially urban areas. Second, the limited facilities for processing waste, the solution is to complete the facilities by innovating using technology with due regard to environmental conditions. Third, to raise public awareness to keep the environment clean, there needs to be ongoing counseling to reduce waste production.